Детство Левы: повесть в рассказах / Б. Д. Минаев - Минаев Борис Дорианович (Книги заветной мечты, 2008)
Экземпляры: ф.1 (2008) / Инвентарный номер: 51925 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 61 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44